Aproveitamento biotecnológico do soro de queijo porungo para obtenção da enzima β-galactosidase - Coelho, Rafaela de Jesus Silva (Universidade Federal de São Carlos, 2020)
Cheese whey are the main by-product of the dairy industry, characterized as an alternative substrate rich in nutrients and applicable in bioprocess. It has a high biochemical oxygen demand (BOD) and when associated with inadequate disposal can lead to several environmental problems. One alternative use of this by-product is in biotechnological processes, such as for the production of β-galactosidase. This study aimed to use porungo cheese whey for β-galactosidase (lactase) production, an enzyme widely applied in the food industry to manufacture lactose-free products. In the first stage of this work, different lines of Kluyveromyces marxianus (CCT 4086 and CBS 6556) and different culture media (porungo cheese whey (S); porungo cheese whey supplemented with yeast extract (SE) and porungo cheese whey supplemented with yeast extract and bacteriological peptone (SEP)) were tested on a rotational shaker at 200 rpm and a temperature of 30 ºC. The best results of enzymatic activity were followed by the strain K. marxianus CCT 4086 in SE (16.73 U mL-1). Therefore, this line was chosen for the second stage, and the influence of the process variables temperature (30ºC and 37ºC) and pH (5, 6 and 7) was evaluated, in a 2 × 3 factorial experimental design. Enzymatic activity reached a maximum value in 20 h of cultivation for all experiments, ranging from 11.41 U mL-1 to 15.93 U mL-1 for temperature of 30 ° C and 10.62 U mL-1 to 13.93 U mL-1 for temperature of 37 ° C. The best process condition was achieved at pH 7.0 and temperature of 30 ºC.
Biotechnological use of porungo cheese whey to obtain the β-galactosidase enzyme
Keywords: Soro de quejo; β-galactosidase; K. marxianus; Bioprocessos; Cheese whey; Bioprocesses; CIENCIAS AGRARIAS::CIENCIA E TECNOLOGIA DE ALIMENTOS::TECNOLOGIA DE ALIMENTOS::APROVEITAMENTO DE SUBPRODUTOS